1998
DOI: 10.1002/(sici)1097-4695(199804)35:1<77::aid-neu7>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Midline fasciclin: ADrosophila fasciclin-I-related membrane protein localized to the CNS midline cells and trachea

Abstract: Drosophila Fasciclin I is the prototype of a family of vertebrate and invertebrate proteins that mediate cell adhesion and signaling. The midline fasciclin gene encodes a second Drosophila member of the Fasciclin I family. Midline Fasciclin largely consists of four 150 amino acid repeats characteristic of the Fasciclin I family of proteins. Immunostaining and biochemical analysis using Midline Fasciclin antibodies indicates that it is a membrane‐associated protein, although the sequence does not reveal a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 44 publications
1
32
1
Order By: Relevance
“…In addition, mfas was expressed in the central nervous system (CNS; Fig. 4C, part III, parts g,h); previous analyses demonstrated that mfas is expressed on the midline neurons and glia in the embryo (Hu et al, 1998). At the level of resolution of our analysis, we are unable to detect expression differences between males and females in the CNS.…”
Section: Development 131 (9)contrasting
confidence: 58%
See 2 more Smart Citations
“…In addition, mfas was expressed in the central nervous system (CNS; Fig. 4C, part III, parts g,h); previous analyses demonstrated that mfas is expressed on the midline neurons and glia in the embryo (Hu et al, 1998). At the level of resolution of our analysis, we are unable to detect expression differences between males and females in the CNS.…”
Section: Development 131 (9)contrasting
confidence: 58%
“…Of the 11 genes ultimately selected, 10 were significant for regulation by dsx according to one or both approaches. The exception was the male gene mfas, which Development 131 (9) Research article the forced-choice model found (though not with significance) more likely to be regulated by fru, and which is known to function in the central nervous system (Hu et al, 1998), as do the male-specific fru products. Having chosen a set of 11 genes, two female and nine male, we proceeded to determine their patterns of expression by in situ hybridization.…”
Section: Selecting Genes For Further Studymentioning
confidence: 95%
See 1 more Smart Citation
“…Periostin has been regarded as a member of the Fasciclin I family, including ␤ig-h3 (Skonier et al, 1992), Algal-CAM (Huber and Sumper, 1994), and midline fasciclin (Hu et al, 1998), mimicking a function of Fasciclin I. Periodontal fibroblasts, major component cells in the periodontal ligament, are able to differentiate into multiple types of cells such as cementoblasts and osteoblasts and appear to play an essential role in response to mechanical forces of the tooth and in repair of a damaged matrix (Lekic and McCulloch, 1996). Although the periodontal fibroblasts have been well-known to have high alkaline phosphatase activity, the periodontal ligament is never calcified under normal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…regarded as a member of the Fasciclin I family, which includes ␤ig-h3 (Skonier et al, 1992), Algal-CAM (Huber and Sumper, 1994), and midline fasciclin (Hu et al, 1998), mimicking a function of Fasciclin I.…”
mentioning
confidence: 99%